Analysis of Factors Affecting Rice Production (A Case Study in Tonra District, Bone Regency): Analisis Faktor-Faktor yang Berpengaruh Terhadap Produksi Padi (Studi Kasus di Kecamatan Tonra, Kabupaten Bone) - Mukarramatul Amriani; Syamsinar; Sulfiana; Helda Ibrahim (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabaya, 2026)
This study was motivated by fluctuating rice production in Tonra District over the past three years, where changes in cultivated area did not always align with output. This suggests that production is influenced by factors beyond land size, such as input use, farm management, environmental conditions, and farmer characteristics. The objective was to identify factors affecting rice production and measure their contribution to production fluctuations. A quantitative survey method was used, collecting data from rice farmers through questionnaires and interviews. The dependent variable was rice production, while independent variables included land area, seed usage, fertilizer, farmer age, and education level. Data were analyzed using multiple linear regression, including t-tests, F-tests, and the coefficient of determination. The t-test results showed that all independent variables simultaneously had a significant effect on production. The F-test revealed that land area and fertilizer had a positive and significant effect, whereas seed usage, age, and education level did not. The coefficient of determination (0.484) indicated that 48.4% of production variation was explained by the model, with the remainder due to unexamined factors. These findings emphasize that increasing rice production in Tonra District primarily depends on optimizing land area and fertilizer use.